The World Wide Web Conference 2019
DOI: 10.1145/3308558.3313548
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Tensor Decomposition for Large Scale Health Analytics

Abstract: In the past few decades, there has been rapid growth in quantity and variety of healthcare data. These large sets of data are usually high dimensional (e.g. patients, their diagnoses, and medications to treat their diagnoses) and cannot be adequately represented as matrices. Thus, many existing algorithms can not analyze them. To accommodate these high dimensional data, tensor factorization, which can be viewed as a higher-order extension of methods like PCA, has attracted much attention and emerged as a promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…These advantages have made tensor decomposition a promising modeling approach to learn abstract patient representations from EHR data and provide good interpretability and scalability [42]. A tensor-based patient representation allows for the capture of complex interactions and relationships between clinical events (especially phenotypes, comorbidities, and medications) that are not evident in flattened EHR data [43].…”
Section: Tensor-based Patient Representationmentioning
confidence: 99%
“…These advantages have made tensor decomposition a promising modeling approach to learn abstract patient representations from EHR data and provide good interpretability and scalability [42]. A tensor-based patient representation allows for the capture of complex interactions and relationships between clinical events (especially phenotypes, comorbidities, and medications) that are not evident in flattened EHR data [43].…”
Section: Tensor-based Patient Representationmentioning
confidence: 99%
“…To reduce the storage resources required by this data, various authors have used tensor-based data decomposition and storage techniques. For instance, He et al [20] proposed a distributed, scalable, and sparse tensor factorization method to provide scalability and accuracy while performing healthcare analytics. Furthermore, Sandhu et al [21] showed the applicability of tensor-based data representation and storage approach on the healthcare diabetes data.…”
Section: Related Workmentioning
confidence: 99%
“…Tensors are higher-order generalization of matrices, and they provide a natural abstraction for complex and inter-related data. Many critical applications, such as data mining [25,38], social network analytics [14,41], cybersecurity [9,13], and healthcare [16,18], generate massive amounts of multidimensional (multi-modal) data as sparse tensors that can be analyzed quickly and efficiently using tensor decomposition (TD). The most popular TD method is the canonical polyadic decomposition (CPD), which approximates a tensor as a sum of a finite number of rank-one tensors such that each rank-one tensor corresponds to a useful data property [5,24].…”
Section: Introductionmentioning
confidence: 99%